Strategies for solving conflicts used by wives of men addicted to alcohol - Chemperek, Agnieszka (Rodzina w systemie wsparcia i pomocy osobom z problemem alkoholowym, 2020)
Introduction: The aim of the article is to present conflict resolution strategies in dealing with alcohol addiction of the husband. The study involved women who are (or were) in a relationship with a person addicted to alcohol. The criterion for the selection of the research sample was to apply to aid institutions in connection with an alcohol problem in the family. In order to determine the conflict resolution strategy, the Strategy for Conflict Resolution Strategy (SRK) was used. The method was constructed by Kriegelewicz (2003), based on the “Patterns of Problem Solving” tool by Rusbult, Johnson and Morrow (1986). The SRK questionnaire measures four ways of responding to conflict situations in marriage: dialogue, loyalty, escalation of the conflict, withdrawal. The above strategies will be analyzed with consideration for such subject variables as: emotional intelligence, sense of coherence, sense of security and resilience as well as personal beliefs. In the article, strategies for resolving conflicts will be treated as one of the determinants of the methods of adaptation to the family situation, which constitute a relationship with a person addicted to alcohol causes changes in the nature of relationships and the quality of communication between spouses, as a result of intensifying conflict situations. The accumulated negative emotions resulting from emotional pain, instances of violence, as well as the burden of family duties on the non-drinking spouse, lead to destructive conflict resolution strategies along with the development of addiction. The presented results show differences in ways of solving conflicts by co-addicted women, depending on situational and subjective variables. The results of the research may be helpful in creating therapeutic goals aimed at strengthening constructive strategies, as well as silencing and changing destructive strategies. These conclusions fit into rehabilitation trends directed at helping couples as part of short-term therapy.